Salmonella contamination frecuency in imported feeding stuffs - ΒΟΓΙΑΖΑΣ Δ. Σ.; ΠΑΝΝΑΚΟΥΛΑΣ Δ. Γ.; ΨΑΝΝΗΣ EMM. Π. (Journal of the Hellenic Veterinary Medical Society, 2019)
In the present study the Salmonella contramination incidence of the imported feeding stuffs in the North Greece during the years 1976-1980 was investigated. The microbiological techniques as well as the results of the present investigation are presented. It was proved that a Salmonella contamination problem in this Country does exist, particularly with serotypes which have been isolated for the first time. From 990 examined samples of feeding stuffs (fishmeal, meat meal and feather meal) 56 samples were found positive for Salmonella (positiveness 5,65%). The results of the present study are compared with those of other respective studies and the probabilities of the dispersion and contamination of the animals as well as of their derivative foods are discussed too.